Solving the Puzzle of Collaborative Governance - Weaver, Liz (Tamarack Institute, 2021)
There is a substantive amount of literature about collaboration and collaborative work but relatively little that identifies the nuts and bolts of collaborative governance including process, structure, accountability, engagement, and effectiveness. This article is for changemakers encountering challenges with collaborative governance within their work.
Keywords: Canada; Libre accès